A strategy for improving the mechanical properties of FSWed joints of non-heat-treatable Al alloys through a combination of water cooling and particle addition. (August 2018) - Huang, Guoqiang; Wu, Jie; Shen, Yifu
Abstract: In this paper, we developed a new process to improve the mechanical properties of FSWed joints of non-heat-treatable Al alloys through a combination of water cooling and particle addition. 5-mm-thick AA5083-H112 non-heat-treatable Al alloy plates were joined by friction stir welding (FSW). The whole FSW process was performed underwater with titanium (Ti) powders incorporated into the nugget zone (NZ), which is referred to as the underwater friction stir powder welding (UFSPW). The microstructure and mechanical properties of the UFSPW joints were investigated, and compared with the conventional FSW joints without Ti particle addition. The results revealed that compared with FSW joint, the area around the NZ of UFSPW joint was much less influenced by the thermoplastic deformation taking place in the NZ. Also, Ti particles with the excellent Ti/Al interfacial bonding, were uniformly scattered into the NZ of UFSPW joint, which was composed of ultrafine recrystallized grains with the average size of ∼0.8 μm. Compared to BM, the NZ of UFSPW joint exhibited markedly improved hardness while the hardness of the NZ of FSW joint increased slightly, with a slight hardness reduction occurring in a local area around the NZ. The YS and UTS of UFSPW joint was significantly increased when compared to that of FSW joint fracturing at the advancing side of NZ, and even up to that of the BM with the fracture occurring at the BM. Such obvious enhancement in strength originates from the creation of ultrafine grains and the well-distributed Ti particles.